Welcome to Westonci.ca, your one-stop destination for finding answers to all your questions. Join our expert community now! Join our Q&A platform and get accurate answers to all your questions from professionals across multiple disciplines. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
(i) If we can write c as a linear combination of a and b, then there exist scalars k₁ and k₂ such that
[tex]c = k_1a + k_2b[/tex]
Solve for k₁ and k₂ :
[tex]3u + 4v = k_1 (3u - v) + k_2 (-u + 2v)[/tex]
[tex]3u + 4v = (3k_1 - k_2) u + (-k_1 + 2k_2) v[/tex]
Then we must have
[tex]\begin{cases}3k_1 - k_2 = 3 \\ -k_1 + 2k_2 = 4\end{cases} \implies k_1 = 2, k_2 = 3[/tex]
and so
[tex]\boxed{c = 2a + 3b}[/tex]
(ii) Given that u and v form an angle of 60° between them, we have by the dot product identity
[tex]u \cdot v = \|u\| \|v\| \cos(60^\circ)[/tex]
where ||u|| denotes the magnitude of the vector u. Both u and v are unit vectors, so ||u|| = ||v|| = 1, and
[tex]u \cdot v = \dfrac12[/tex]
A special case of the identity with u = v tells us that for any vector u,
[tex]u \cdot u = \|u\|^2 \cos(0^\circ) = \|u\|^2[/tex]
which means
[tex]u \cdot u = v \cdot v = 1[/tex]
This in turn means we have
[tex]a \cdot a = (3u - v) \cdot (3u - v) = 9 (u \cdot u) + (v \cdot v) - 6 (u \cdot v) = 7[/tex]
[tex]a \cdot b = (3u - v) \cdot (-u + 2v) = -3 (u\cdot u) - 2 (v \cdot v) + 7 (u \cdot v) = -\dfrac32[/tex]
[tex]a \cdot c = (3u - v) \cdot (3u + 4v) = 9 (u\cdot u) - 4 (v\cdot v) + 9 (u \cdot v) = \dfrac{19}2[/tex]
[tex]b\cdot b = (-u + 2v) \cdot (-u + 2v) = (u \cdot u) + 4 (v\cdot v) - 4 (u \cdot v) = 3[/tex]
[tex]b\cdot c = (-u + 2v) \cdot (3u + 4v) = -3 (u\cdot u) + 8 (v\cdot v) + 2 (u\cdot v) = 6[/tex]
[tex]c \cdot c = (3u + 4v) \cdot (3u + 4v) = 9 (u\cdot u) + 16 (v\cdot v) + 24 (u\cdot v) = 37[/tex]
and hence
[tex]d \cdot d = (3a + 2b + c) \cdot (3a + 2b + c)[/tex]
[tex]d \cdot d = 9 (a\cdot a) + 4 (b\cdot b) + (c \cdot c) + 12 (a\cdot b) + 6 (a\cdot c) + 4 (b\cdot c)[/tex]
[tex]d\cdot d = 175[/tex]
and so ||d|| = √175 = 5√7.
We appreciate your visit. Hopefully, the answers you found were beneficial. Don't hesitate to come back for more information. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Get the answers you need at Westonci.ca. Stay informed by returning for our latest expert advice.